Idea Web Strategy on the Reading Comprehension of EFL Learners: An Enhancement Model - Maravilla, Wes Harven Guillemer (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study quantitatively investigated the impact of integrating writing tasks, specifically the Idea Web strategy, into EFL reading instruction for Taiwanese senior high school students. The research employed a three-group quasi-experimental design to compare the effectiveness of different reading strategies on students' comprehension. 24 participants were divided into three groups of 8 members each: Reading with Summarizing, Reading with Journalizing, and a control group using a conventional oral discussion strategy. Reading comprehension was measured using pre- and posttests. The quantitative results demonstrated that integrating writing tasks, particularly summarizing and journalizing, led to significant improvements in students' reading comprehension compared to the traditional approach. This suggests that incorporating active writing strategies enhances reading comprehension more effectively than conventional methods in EFL contexts.